From Mystical Exegesis to Mental Well-Being: Rūzbihān al-Baqlī’s Theory of Dhikr in Light of Q. 2:152 and Its Resonance in the Lived Experiences of Acehnese Dayah Scholars - Syamaun, T. Ibrahim; Said, Hasani Ahmad; F. Saenong, Faried (Program Studi Ilmu Al-Qur'an dan Tafsir Fakultas Ushuluddin dan Filsafat, UIN Ar-Raniry, 2026)
Although numerous studies have associated dhikr with psychological well-being, most explain its benefits either through psychological coping models or normative theological perspectives, leaving the hermeneutical foundations of classical Sufi exegesis largely unexplored. This study asks how Rūzbihān al-Baqlī conceptualizes dhikr in his interpretation of Q. 2:152 and whether this hermeneutical framework resonates with the lived experiences of Acehnese dayah scholars. Employing a qualitative design, the study combines textual hermeneutics of ʿArāʾis al-Bayān fī Ḥaqāʾiq al-Qurʾān with phenomenological inquiry based on semi-structured interviews analyzed within the perspective of lived religion. The findings indicate that Rūzbihān presents dhikr as a transformative movement from verbal remembrance toward sustained awareness of divine presence, while participants consistently describe dhikr as fostering emotional stability, resilience, gratitude, and inner tranquility through continuous consciousness of God. Rather than establishing direct empirical confirmation of every mystical stage proposed by Rūzbihān, the interview data demonstrate a strong conceptual resonance between his hermeneutical model and contemporary religious experience. The study concludes that psychological well-being is best understood as an emergent consequence of spiritual transformation, offering a Qur'anically grounded model that connects classical Sufi exegesis, lived religion, and contemporary discussions of mental well-being.